IMPLEMENTATION OF PROFILE MATCHING METHOD IN DECISION SUPPORT SYSTEM SMARTPHONE SELECTION BASED ON CONSUMER NEEDS - Muth’mainnah, , A. (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2023)
Smartphones are Internet-enabled phones and typically provide Personal Digital Assistant (PDA) functions such as calendar functions, to-do books, address books, calculators, and notes. At first, the smartphone is a rare item and considered luxurious. However, the lack of community information about smartphone specs also greatly affects the selection of smartphones they will use. Smartphones have a variety of specifications such as processor speed, clear screen, battery life, camera strength, and storage space that makes people tend to be confused in buying a smartphone. For that people need a computerized system that can assist consumers in obtaining a decision to choose a smartphone that suits the wants and needs. Decision Support System (SPK) is a process of selecting alternative actions to achieve a specific goal or goal. SPK is used as a tool for decision-makers to develop decision-making capabilities, but not to replace judgments of decision makers. This SPK test uses Profile Matching Method by looking at the calculation of Criteria Weight Value, Calculation of Sub-Criteria Weight Value, Gap Value calculation, Core Factor and Secondary Factor calculation, and Total Value Ranking Calculation. The end result of this system is ranking the existing smartphone according to the criteria that the buyer has input. Keywords: Smartphone, SPK, Decision Support System, Core and Secondary Factor